The Impact of Global Technological Change on Medium and Lower Skilled Textile and Garment Workers in Thailand - Nazrul Islam (Asian Academy of Management Journal, 2001)
This paper examines the effect of technological change on job security, job satisfaction, work relations and the overall socio-economic situation of medium and lower skilled textile and garment workers in Thailand. It also investigates the influence of job security, job satisfaction, and work relations on the overall situation of workers. Result show that the work pride, supervisions quality, benefits, internal communication, fair pay, workers involvement in the change process, personal control and the overall situation are positively influenced by the technological change. The negative effects are increased skill demands, workload, complexity in work assingment, and strikes. Unskilled textile workers are more involved in downsizing from the change than garments workers are. The more skill demands and more frustration leads to a less positive overall impact on workers. The more involvement of workers in the change process and more personal control over their work result in more postive overall impact. Job satisfaction factors are not significantly related to the overall impact. However, job security, job satisfaction and work relations together are significantly related to the overall socia-economic impact of technological change on Thai workers.